Correlation of Fast Food Consumption and Overweight/Obesity among Undergraduate Students at the University of Hargeisa in Hargeisa, Somaliland - Mohamed, Abdi Abdilaahi; Solomon, Gebretsadik Bereka (International Journal of Eating and Weight Disorders, 2025)
Background Fast food consumption is the major cause of obesity and overweight in worldwide affecting more than 2 billion people, especially developing countries and low income countries. It can lead to hyperinsulinemia and development of insulin resistance, high energy density, high glycemic index, and fatty acid composition of fast foods may increase the prevalence of obesity and cardiovascular risk factors Objectives The main aim of this study was, to assess fast food consumption and its association with overweight /obesity among undergraduate students of University Hargeisa, Somaliland, 2023. Methods The study was carried out from May 01 to July 20, 2023 at University of Hargeisa using an institutional based cross-sectional study design to among 260 students. The study participants were selected using a simple random sampling technique. A structured questionnaire was prepared based on review literatures and dig out from related studies. The anthropometric data was taken by data collectors to measure weight and height using a stadiometer. Data was entered and checked for errors using EPI-info version 7.1.5.0 and then, data were exported to statistical package for social sciences (SPSS) software version 21 and STATA software version 14 for data processing and analysis. Descriptive statistics such as; frequencies, means and proportion was used for present the findings. A variable with P-values of less than 0.25 in the binary logistic regression analysis was entered into a multivariable logistic regression analysis to identify the independent predictors of stunting. Finally, variable at P-value less than 0.05 in multivariable logistic regression analysis was considered as a statistically significant variable. Results In this study, the majority 235 (90.4%, CI: 86.5- 93.8) of the study participants were fast food consumers. The study revealed that, from the total study participants 46(17.7%),127(48.8%),84(32.3%), 3(1.2%) were underweight, normal, overweight and obese respectively. A chi-square test revealed that there was a significant (p-value=0.058) associations between BMI and fast food consumption among students of University of Hargeisa. On multi-variable logistic regression model educational level of the students (AOR = 12.45 (95% CI: 1.7, 14.6)) and frequency of fruit (AOR = 0.76, 95% CI (0.7, 0.8)) and vegetable consumptions (AOR = 0.51, 95% CI (0.47, 0.575)) were found to be significantly associated with fast food consumptions (p < 0.05). Conclusion In this study, of the total 90.4% number of fast food consumers. A chi-square test revealed that there was a significant (p-value=0.058) associations between BMI and fast food consumption among students of University of Hargeisa. Educational level of the students and frequency of fruit and vegetable consumptions were found to be significantly associated with fast food consumptions. Effort should be made to increase access to fast food-related information and counseling.
Keywords: Fast food consumption; Overweight/Obesity; University of Hargeisa; Somaliland